Mire’s Interpretation of the Tragic and Paradoxical World of Oscar Wilde - Mikhailova, Maria; Kudritskaya, Sofya (Literatūra, 2021)
This article analyzes the reception of the figure of O. Wilde, the 19th-century English writer, and his works in the prose and criticism of Alexandra Mikhailovna Moiseeva (1874-1913), who entered the history of Russian literature of the Silver Age by the name of “Mire”. The study focuses mainly on her story Black Panther (1909), in which the author provides an original perspective on the tragic love episode in Wilde’s life. Attention is also paid to the thematic similarities between the works of Wilde and Mire in terms of genre, plot and literary image, as well as Mire’s interpretation of Wilde’s works in her critical reviews.
Keywords: Wilde; Mire; The Picture of Dorian Gray; Black Panther; paradoxical; aestheticism; automif; decadence; symbolism; irony